Long and short por cointegração aplicado ao mercado acionário brasileiro - Cardoso, Clézio Lopes (Universidade Federal de São Carlos, 2023)
In this article, we conduct a detailed analysis of the long and short investment strategy with cointegration in the Brazilian stock market. We explore the correlation between pairs of stocks and propose a trading approach that capitalizes on temporary deviations from this relationship. The strategy involves buying the undervalued stock and selling the overvalued one. Through the application of advanced statistical techniques and empirical analysis, we demonstrate that this approach can generate significant risk-adjusted returns. The article discusses the implications of these results for investors and offers valuable insights to enhance investment strategies. This study contributes to financial literature by presenting a new perspective on the application of cointegration in the long and short strategy.
Long and short by cointegration applied to the brazilian stock market
Keywords: Cointegração; Investimento; Long-short; Trading; Cointegration; Investiment; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA::INFERENCIA EM PROCESSOS ESTOCASTICOS